2015
DOI: 10.1080/10826076.2014.999868
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Kinetics of Cyazofamid in Water

Abstract: A reliable and sensitive method has been developed and validated for the determination of cyazofamid in water using reverse phase HPLC (RP-HPLC). The analytical procedure involves fortification of water at two doses, liquid-liquid partition with chloroform, separation on Discovery C-18 column using mobile phase acetonitrile: water (60:40 v/v) and detection at 279 nm. Calibration curves for quantification were linear over the dynamic range of 0.01-10.0 µg mL À1 concentrations with the correlation coefficients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous studies have already shown that CCIM appears to be more acutely toxic than cyazofamid ( European Food Safety Authority 2016). LC as well as LC–MS have been used to analyse cyazofamid and CCIM. Dissipation of cyazofamid has been determined in tobacco and tomato .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already shown that CCIM appears to be more acutely toxic than cyazofamid ( European Food Safety Authority 2016). LC as well as LC–MS have been used to analyse cyazofamid and CCIM. Dissipation of cyazofamid has been determined in tobacco and tomato .…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated residues of metalaxyl or cyazofamid in crops using high‐performance liquid chromatography (HPLC) (Lee et al, ; Malhat, ; Singh & Tandon, ; Tandon & Singh, ; Zheng, Feng, Ge, Lv, & Xie, ), ultra‐performance liquid chromatography (Liu et al, ), gas chromatography (GC) (Rani, V. K. Sharma, Rattan, Singh, & Sharma, ; Rattan & Sharma, ) and liquid chromatography with tandem mass spectrometry (LC‐MS/MS) (Lee et al, ; Li et al, ; Ramezani & Shahriari, ; Zhu et al, ). For example, Zheng et al () used a QuEChERS (quick, easy, cheap, effective, rugged and safe) HPLC method to detect trace amounts of metalaxy in watermelon, and the average recovery rates were between 92.20 and 98.90%.…”
Section: Introductionmentioning
confidence: 99%